Nationalization and privatization in modern economy - Salayeva Quvonchoy Rustam qizi (Euro Asian Journal Publishing, 2023)
This article is devoted to deep analysis and comparison between nationalization and privatization which are two economic policies that transfer ownership and control of assets from the public sector to the private sector or vice versa. Nationalization is when the government controls private companies or assets, making them the state's property. The transfer of ownership, property or business from the government to the private sector is termed privatization. The government ceases to be the owner of the entity or business. The process in which a publicly-traded company is taken over by a few people is also called privatization
Keywords: nationalization; privatization; ownership; transferring